2023
DOI: 10.1002/mnfr.202300009
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Pharmacokinetic Modeling of the Postbiotic Supplement Urolithin A Predicts its Bioavailability Is Orders of Magnitude Lower than Concentrations that Induce Toxicity, but also Neuroprotective Effects

Abstract: Scope A range of health benefits are attributed to consuming urolithin A (UA), such as improved muscle health, anti‐aging activity, and neuroprotection, whereas few studies raise possible adverse effects at high doses, including genotoxicity and estrogenic effects. Therefore, understanding UA bioactivity and safety depends on its pharmacokinetics. However, there is no physiologically‐based pharmacokinetic (PBPK) model available for UA, thus limiting reliable assessment of effects observed from in vitro experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Significantly, the UA concentration was 1.68 ± 0.25 ng/g in brain tissue and 18.75 ± 3.21 ng/mL in plasma [26]. Only recently, physiologically based pharmacokinetic modelling of the postbiotic supplement UA for predicting its bioavailability confirmed one-digit nanomolar concentrations in the brain [96]. The results contribute to the idea of UA crossing the BBB [79,80,97] and being the neurologically active metabolite of pomegranate juice [26,79].…”
Section: Parkinson's Diseasementioning
confidence: 87%
See 1 more Smart Citation
“…Significantly, the UA concentration was 1.68 ± 0.25 ng/g in brain tissue and 18.75 ± 3.21 ng/mL in plasma [26]. Only recently, physiologically based pharmacokinetic modelling of the postbiotic supplement UA for predicting its bioavailability confirmed one-digit nanomolar concentrations in the brain [96]. The results contribute to the idea of UA crossing the BBB [79,80,97] and being the neurologically active metabolite of pomegranate juice [26,79].…”
Section: Parkinson's Diseasementioning
confidence: 87%
“…Regarding PD, given the recent advancement in detecting prodromal individuals before diagnosis and the potential prognostic value of the α-synuclein biomarker, research into selecting the right time for UA intervention shows promise to delay PD onset or progression to people at an increased risk [102]. Nevertheless, as predicted by computer modelling, low brain bioavailability of UA is orders of magnitudes lower than concentrations that provide neuroprotective effects [96], and thus should be managed by any supplementation scenario. Advanced nutritional approaches enabling the delivery of UA in a calibrated manner are likely to play a key role in bridging the gap created by the natural heterogeneity of the gut microbiome to deliver health benefits.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…In recent years, physiologically based pharmacokinetic (PBPK) modeling has become an interesting alternative to animal testing, making use of existing physicochemical data and in vitro metabolism data in order to determine the tissue concentrations of chosen compounds. As an example, in a recent study of a PBPK model regarding the post-biotic supplementation of Uro-A, it was suggested that peak concentrations in most tissues were low (nanomolar range), supporting the safety of Uro-A to be used as a post-biotic supplement [198].…”
Section: Bioavailability Of Uros and Their Metabolitesmentioning
confidence: 99%